Blockchain ledger application for Graffiti digitalization (2021)
As we leave the 2020s and enter a new decade, technology will keep on giving us creative and varied ways of solving different problems, as an example, the creation and implementation of blockchain have shown to be a reliable solution to many problems and a potentially great solution candidate to the problem previously stated. The reasons will be exposed in this dissertation, but as an entrée, we can say that it is because it is a distributed system that safeguards and enables people to appreciate the graffiti works stored in its interior. The creation of a new market and the involvement of society, graffiti artists, the government, the buyers, and the blockchain platform, create a unique environment where benefits for every party can be seen everywhere. Not only can blockchain provide an effective solution to the problem, but also it may support local artists and the city and help explore new creative paths to society.